Simulasi Sensor Parkir Berbasis Mikrokontroler Arduino Uno dengan Sensor HC-SR04 Menggunakan Website Wokwi - Qonita Auliani; Riyan Aditya; Muhammad Dicky Saputra; Muhammad Aldi Firdaus; Bryant Reza Pahlevi; Didik Aribowo (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the design and simulation of an Arduino Uno microcontroller-based parking sensor system that uses HC-SR04 ultrasonic sensors to detect the distance of objects in the parking area. The project is implemented and tested through the Wokwi online simulation platform. This approach aims to provide an effective solution in prototyping parking sensor systems that is cost-effective and easily accessible. Simulation using Wokwi allows the development and testing of code and electronic circuits without physical hardware, making it easier to test the functionality of sensors and microcontrollers. Simulation results show that the HC-SR04 sensor can detect distance with sufficient accuracy and activate notifications based on a certain distance, which is relevant in the application of automated parking systems.